2014
DOI: 10.1186/s12992-014-0079-3
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for cost-effectiveness of lifestyle primary preventions for cardiovascular disease in the Asia-Pacific Region: a systematic review

Abstract: BackgroundCountries of the Asia Pacific region account for a major share of the global burden of disease due to cardiovascular disease (CVD) and this burden is rising over time. Modifiable behavioural risk factors for CVD are considered a key target for reduction in incidence but their effectiveness and cost-effectiveness tend to depend on country context. However, no systematic assessment of cost-effectiveness of interventions addressing behavioural risk factors in the region exists.MethodsA systematic review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
(169 reference statements)
0
6
0
1
Order By: Relevance
“…Our qualitative study found that the community residents sprinkled table salt on rice because they liked the salty taste and served salt with meals for welcoming guests. 16 While salt reduction is known to be a cost effective strategy to prevent cardiovascular diseases, 38 39 it is difficult to modify the dietary habits of individuals in a short time period. Thus, a long-term community-wide campaign to modify the diets of community residents is necessary, as shown in successful model programmes in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Our qualitative study found that the community residents sprinkled table salt on rice because they liked the salty taste and served salt with meals for welcoming guests. 16 While salt reduction is known to be a cost effective strategy to prevent cardiovascular diseases, 38 39 it is difficult to modify the dietary habits of individuals in a short time period. Thus, a long-term community-wide campaign to modify the diets of community residents is necessary, as shown in successful model programmes in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…However, without sustained compliance of subjects with advocated lifestyle changes, weight regain over the long-term can alter the quality of life and impinge on the estimated cost-effectiveness of interventions. Considering exclusively the short-term effects of obesity control interventions can indeed be misleading [ 49 ]. For this reason, it is not impossible that the cost-effectiveness of some interventions reviewed here and focusing on obesity was overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…The search strategy was informed by a scoping review that covered relevant reviews on economics studies of PA, 17–23 reviews on PA 24–26 and reviews on economic evaluations. 27–29 The final search strategy including search terms for each database is given in online supplemental file 2 .…”
Section: Methodsmentioning
confidence: 99%